Espiritualidade e saúde no processo de recuperação de mulheres, em situação de dependência química por meio da biodanza - Santos, Carmen Lúcia dos (2020)
The present work ,elaborated in the scope of the Sciences of Religions from the line of research on Spirituality and Health, has as objective to show the applicability of the experiences in“Biodanza“ as empowering in the process of the recovery of chemically dependent street women welcomed at Bethany House in the City of Maceió-Al. Rolando Toro’s “Biodanza”(1991; 2002; 2005; 2009a; 2009b; 2014) is presented as a system of organic renewal based on its five experiential lines ,namely: vitality, sexuality, creativity, affectivity and transcendence. It is a qualitative research based on the Focus Group technique (FG). This technique brings an understanding of the object within its context in addition to being a procedure that allows the collection of information through group interaction. The theoretical framework about spirituality and health in a holistic vision of the Integral Being is based on the vision of Possebon (2017), Rörh (2012) Dethlefsen and Dahlke (2007) and Fowler (1992) among other authors who support this study. The results show that there was a need to adapt Toro’s traditional method from one to two weekly sessions in consideration of the group of addicted women. It was also verified, through the data obtained, that Biodanza contributes to the physical, psychological and spiritual well-being of these women, as well as impressing upon them an increase in their capacity for internalization and the vitalization of energy, improving also their relationship with nature. Other relevant aspects are the strengthening of self-esteem and the incentive to live a dignified life free from drugs. Finally, it was registered that there exists a relationship between Biodanza and spirituality since the reports point to the development of these practices that empower the human being in an integral way.